Speculations on the subject of alcohol dehydrogenase and its properties in Drosophila and other flies. - Ashburner, M. (BioEssays, 1998)
The alcohol dehydrogenases (ADH) and their genes (Adh) of Drosophila have been much studied by population and evolutionary biologists. I attempt to put some of these studies into a broad adaptionist perspective, suggesting the co-evolution of this enzyme with the fleshy fruits of angiosperms and fermenting yeasts. I suggest that these events occurred at about the K/T boundary (65 million years ago) and that the typical Drosophila (as exemplified by D. melanogaster) evolved from flies unable to use fermenting substrates as breeding sites. I also hint that the ADH enzymes of other flies (e.g., the tephritid fruit flies) may have evolved independently of those of Drosophila, but from a common ancestral gene.